SiO2 (at) ZnO white dustproof coating prepared based on step-by-step sol-gel method and preparation method of SiO2 (at) ZnO white dustproof coating
By loading silica and low surface energy modifiers on the surface of the ZnO thermally controlled coating, superhydrophobic SiO2@ZnO particles are formed, which solves the problem of thermal control performance degradation of existing thermal control coatings under lunar dust pollution, realizes the dual functions of thermal control and dust prevention of the coating, and improves the protection effect of the spacecraft in extreme environments.
Patent Information
- Application Number
- CN202411757381.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
AI Technical Summary
The existing thermal control coatings have deteriorated their thermal control performance under lunar dust pollution, lack dust resistance, and it is difficult to effectively protect spacecraft in extreme environments.
Through the step-by-step sol gel method, silica is loaded on the surface of the ZnO thermally controlled coating, the combination of multi-scale particles is constructed, and superhydrophobic SiO2@ZnO particles are formed, thereby achieving thermal control and dust-proof versatility of the coating.
Under the conditions of lunar dust pollution, the SiO2@ZnO coating maintains good thermal control performance and has dustproof performance, effectively reducing lunar dust adhesion and improving the stability of the spacecraft surface thermal management.
Smart Images

Figure CN119592110A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of special functional materials for space, and specifically, relates to a white coating combining dustproof and thermal control functions and a preparation method thereof, which can be applied to the field of deep space exploration and has very broad application prospects. Background Art
[0002] Spacecraft must withstand extreme space environments during deep space exploration missions. In the space environment, spacecraft are exposed to sunlight, which causes extreme changes in the surface temperature of the spacecraft and causes failure of internal precision devices. Therefore, the thermal control system is one of the important guarantee systems for the normal operation of spacecraft. Using thermal control materials for protection is the main way for spacecraft to maintain temperature stability. Paint-type thermal control coatings have become the most commonly used type of thermal control materials in spacecraft due to their low cost, low implementation difficulty, and high surface universality. The moon is the closest celestial body to the earth. The implementation of the lunar exploration project has a positive driving effect on scientific and technological innovation and the development of human civilization. It is a key step for humans to explore the universe. In the process of exploration, it is inevitable to encounter some severe challenges. In addition to the extreme temperature environment, the lunar surface environment must also be considered during the exploration of the moon. Due to the effects of cosmic rays, solar wind, and meteor impacts on the lunar surface, a layer of fine granular weathering material is distributed on the lunar surface, called lunar dust. The lunar dust surface carries a certain charge and has sharp edges, which can easily adhere to the thermal control coating, thereby affecting the thermal control performance of the thermal control coating, causing the spacecraft surface thermal management to fail, and increasing the risk of failure of the lunar exploration mission. Therefore, it is of far-reaching significance to conduct research on the protection performance of lunar dust based on the research on thermal control coatings.
[0003] Paint-type thermal control coatings are composed of pigments and binders. ZnO has a bandgap of 3.37 eV and a refractive index of about 2. It can efficiently reflect sunlight within the solar spectrum and is cheap and easy to obtain. Therefore, ZnO thermal control coatings are the most commonly used. Considering that the space environment will be exposed to ultraviolet radiation, the organic binder will break and degrade chemical bonds, resulting in a decrease in coating performance. Therefore, silica sol is selected as a binder to manufacture ultraviolet radiation-resistant ZnO thermal control coatings. Common ZnO thermal control coatings are easily contaminated by lunar dust, causing degradation of thermal control performance. Summary of the invention
[0004] Existing technologies and materials rarely take into account the possibility of thermal control coatings being contaminated by lunar dust. The basic performance of thermal control coatings is single and they face the risk of performance degradation.
[0005] Traditional thermal control material design only considers pigment modification or single thermal control performance modification of binders, and rarely adopts multifunctional coating design solutions, resulting in limited coating applications. The present invention uses a step-by-step sol-gel method to achieve a ZnO thermal control coating with super-hydrophobic properties, thereby realizing the preparation of a thermal control and dust-proof multifunctional coating, thereby achieving stable performance of the thermal control coating under lunar dust pollution.
[0006] In addition, some researchers have studied the structural synergy of multifunctional coatings. To achieve the super-hydrophobic performance of the coating, the coating only needs to have a rough structure of micro-nano scale, while the thermal control coating requires a particle size of hundreds of nanometers, which is far beyond the rough scale required for the super-hydrophobic coating. There is a contradiction between the thermal control performance of the coating and the rough structure scale regulation of the dust removal performance, and it is impossible to ensure that the dust removal performance and thermal control performance of the material are achieved at the same time. The present invention realizes the coordination of multi-scale particles by loading tens of nanometers of silicon dioxide on the surface of hundreds of nanometers of ZnO, and realizes the super-hydrophobic performance of the coating while ensuring the thermal control performance of the thermal control coating, thereby giving the thermal control coating a certain dustproof performance.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] The present invention provides a novel method for preparing a SiO2@ZnO white dustproof coating based on a step-by-step sol-gel method, wherein SiO2 particles are introduced onto the surface of zinc oxide by a sol-gel method to construct a rough surface structure at the microscopic level, and a low surface energy modifier is added to a mixed solution of zinc oxide and silica sol, mixed evenly, and dried to obtain multi-scale hydrophobic SiO2@ZnO particles. The SiO2@ZnO powder material is put into the silica sol prepared in advance, a surfactant is added, and mixed evenly to form a white slurry, and finally the slurry is covered on an alloy substrate by a scraping technique, and after curing, a SiO2@ZnO white dustproof coating is formed. Specifically, the following steps are included:
[0009] Step 1, uniformly dispersing ZnO in anhydrous ethanol to obtain a ZnO dispersion;
[0010] Mixing ammonia water and tetraethyl silicate, adjusting the pH value and stirring evenly to obtain a sol;
[0011] Then, the sol is added into the ZnO dispersion and stirred evenly;
[0012] Step 2, then add a low surface energy modifier, continue stirring for a certain period of time, centrifuge, wash with anhydrous ethanol and deionized water in turn, and dry to obtain hydrophobic SiO2@ZnO particles;
[0013] Step 3, mixing the hydrophobic SiO2@ZnO particles with the silica sol, adding a surfactant, and stirring evenly to obtain a slurry;
[0014] Step 4: After the metal substrate is cleaned, the slurry is evenly scraped on the metal substrate and cured to obtain the coating.
[0015] It is further defined that in step 1, the pH value of the sol is 8-10, for example, pH=8, pH=9, pH=10, etc.
[0016] It is further defined that in step 1, the mass ratio of zinc oxide to sol is 3:1-1:3. , for example, 3:1, 2:1, 1:1, 1:2, 1:3, etc.;
[0017] It is further defined that in step 1, the ZnO particle size is 200nm-600nm, such as 200nm, 300nm, 400nm, 500nm, 600nm, etc.;
[0018] It is further defined that in step 1, the stirring time is 1-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.
[0019] It is further defined that in step 2, the low surface energy modifier is one of hexamethyldisilazane, heptadecafluorodecyltrimethoxysilane or octadecyltriethylsilane.
[0020] It is further defined that in step 2, the concentration of the low surface energy modifier is 1 wt% to 5 wt%, for example, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, etc.
[0021] It is further defined that in step 2, the stirring time is 1-5 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, etc.
[0022] It is further defined that in step 2, the centrifugation rate is 3000-7000 rpm, for example, 3000 rpm, 4000 rpm, 5000 rpm, 6000 rpm, 7000 rpm, etc.
[0023] It is further defined that in step 3, the pH value of the silica sol is 2 to 5, for example, pH=2, pH=3, pH=4, pH=5, etc.;
[0024] It is further defined that in step 3, the pigment-to-base ratio is 1:1-1:5, for example, 1:1, 1:2, 1:3, 1:4, 1:5, etc.
[0025] It is further defined that in step 3, the surfactant is one of polyvinylpyrrolidone (PVP), cetyltrimethylammonium bromide (CTAB), and cetyltrimethylammonium chloride (CTAC).
[0026] It is further defined that in step 3, the stirring rate is 1000-3000 rpm, for example, 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, etc.
[0027] It is further defined that in step 3, the stirring time is 1-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.
[0028] It is further defined that in step 4, the metal substrate is an aluminum alloy, a titanium alloy or a magnesium alloy;
[0029] It is further defined that in step 4, the coating thickness is 100 μm-300 μm, for example, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, etc.
[0030] It is further defined that in step 4, the curing temperature is 60-100°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, etc.
[0031] A SiO2@ZnO white dust-proof coating prepared by any of the above methods.
[0032] In response to the problem of lunar dust pollution, the current protection methods can be divided into two types: active protection and passive protection technology. Active protection technology often requires additional energy support, while passive protection technology is more convenient. The adhesion between dust and the surface is divided into three types: van der Waals force, electrostatic force and capillary force. Moon dust has the characteristics of small particle size and high surface energy. When it comes into contact with the solid surface, it has a great van der Waals force, exhibits strong adhesion, and is very easy to adhere to the thermal control surface. When studying the passive protection of lunar dust, van der Waals force can be used as the main consideration. When studying the passive protection performance of lunar dust, it is usually considered from the perspective of reducing van der Waals force, and the coating surface is physically or chemically pretreated to have extremely low surface energy and micro-nano scale rough structure, which can effectively reduce the van der Waals force and reduce dust adhesion. Therefore, while constructing the thermal control coating, it is possible to consider giving the coating extremely low surface energy and micro-nano scale rough structure, and then develop a ZnO white coating to achieve the dustproof performance of the thermal control coating, which provides certain guidance for the effective thermal management of spacecraft in the space environment.
[0033] Super hydrophobic coating is a kind of material with special performance surface, which can reduce the van der Waals force while having super hydrophobic performance, and effectively realize dustproof effect. At present, the preparation method commonly used in super hydrophobic coating has hydrothermal method, etching method, vapor deposition method, sol-gel method, etc. Compared with other methods, sol-gel method is simple to operate, mild experimental conditions, low cost, can be prepared on a large scale, suitable for industrial production, and it is practical value to study the preparation of super hydrophobic coating by sol-gel method. Sol-gel method is to use metal alkoxide or alkoxy metal as precursor, acid and alkali as catalyst, alcohol as solvent, and form sol system by hydrolysis reaction and condensation reaction, and then the generated gel is dried to form nanoporous structure. In sol-gel method, the stoichiometric ratio of each substance is easy to control, and the coating can realize the uniformity of molecular level in a short time, and the reactants are uniformly mixed at the molecular level, and the prepared sol purity is higher, with good stability. Therefore, it is selected to prepare ZnO white dustproof coating by sol-gel method with practical application value.
[0034] The present invention proposes a multifunctional coating integrating dustproof and thermal control functions. Through a step-by-step sol-gel method, on the basis of realizing a ZnO thermal control coating, the coating is made to have super-hydrophobic properties, thereby achieving dustproof adhesion without affecting the thermal control performance of the thermal control coating.
[0035] The present invention realizes the coordination of multi-scale particles by loading ten-nanometer-sized silicon dioxide on a hundred-nanometer ZnO surface, controls the process parameters of the sol-gel to adjust the amount and morphology of the silicon dioxide loaded on the ZnO surface, thereby controlling the micro-nano-sized rough structure on the pigment surface, and simultaneously adds a low surface energy modifier to obtain hydrophobic SiO2@ZnO particles. When lunar dust contacts the SiO2@ZnO surface, the SiO2@ZnO surface has a certain rough structure, and the micro-convex structure on the surface can reduce the contact area between the dust particles and the SiO2@ZnO surface. Moreover, under the action of the low surface energy modifier, the solid surface energy of SiO2@ZnO is low, the dust has a low van der Waals force with the surface, and exhibits low lunar dust adhesion, thereby realizing the dust-proof performance of the thermal control coating.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The present invention is based on a step-by-step sol-gel method. First, multi-scale hydrophobic SiO2@ZnO particles are obtained by a sol-gel method. The SiO2@ZnO powder material is put into a pre-prepared silica sol, a surfactant is added, and the mixture is uniformly mixed to form a white slurry. Finally, the slurry is coated on an alloy substrate by a doctor blade technique. After curing, a SiO2@ZnO white dustproof coating is formed. The process conditions and the pigment-to-base ratio of the slurry modified by the two-step sol-gel method can control the composition and surface morphology of the coating material.
[0038] The coating selects multi-scale SiO2@ZnO as the pigment. The large-particle ZnO and the small-particle ZnO loaded on the surface work together to give the white coating excellent thermal control and dust-proof effects.
[0039] In addition, the white coating has a low solar absorption ratio and high emissivity, stable structural performance under extreme conditions (pressure, temperature, irradiation), and excellent mechanical properties. It is suitable for the actual mission environment of spacecraft and can be used in deep space exploration and other fields.
[0040] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The solar spectrum absorption test results of the SiO2@ZnO-A white coating prepared in Example 1 of the present invention;
[0042] Figure 2 The spectral emission test results of the SiO2@ZnO-A white coating prepared in Example 1 of the present invention;
[0043] Figure 3 This is a graph showing the coating adhesion test results of the SiO2@ZnO-A white coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0044] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, and do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0045] Example 1: SiO2@ZnO-A coating
[0046] The invention provides a method for preparing a novel SiO2@ZnO white dustproof coating based on a step-by-step sol-gel method. The coating firstly obtains multi-scale hydrophobic SiO2@ZnO particles by a sol-gel method, and the SiO2@ZnO particles are uniformly mixed with silica sol prepared in advance. The coating is scraped on an alloy substrate by a scraping technique to obtain a white slurry obtained by scraping the SiO2@ZnO and silica sol.
[0047] 1. The preparation of multi-scale hydrophobic SiO2@ZnO particles is as follows:
[0048] 200nm ZnO was selected as the pigment matrix, 20g ZnO was uniformly dispersed in 60g ethanol, ammonia water was mixed with tetraethyl silicate, pH was adjusted to 9 to prepare a sol, and the sol was further stirred for 2 hours to complete premixing. After that, the sol was added to the previous ZnO ethanol mixture at a ratio of 3:1, and continued to stir for 1h to ensure uniform mixing, a certain amount of hexamethyldisilazane was added to the mixture, and continued to stir for 3h, and the mixture prepared above was also centrifuged at a speed of 5000rpm, and washed three times with ethanol and deionized water, and dried to obtain multi-scale hydrophobic SiO2@ZnO particles.
[0049] 2. Prepare SiO2@ZnO white slurry:
[0050] Prepare silica sol with pH = 4 as a binder, set the pigment-to-base ratio to 1:4, set the speed of the cutting mixer to 2000 rpm, and stir at room temperature for 2 hours. Select aluminum alloy as the metal substrate, and ultrasonically clean the sandblasted aluminum alloy substrate with acetone and anhydrous ethanol. After the slurry is evenly stirred, it is evenly coated on the aluminum alloy substrate by scraping. The coating thickness is 150 μm and cured in an oven at 80°C for 4 hours.
[0051] Example 2: SiO2@ZnO-B coating
[0052] 400nm ZnO was selected as the pigment matrix, 20g ZnO was uniformly dispersed in 60g ethanol, ammonia water and tetraethyl silicate were mixed, pH was adjusted to 9 to prepare a sol, and the sol was further stirred for 2 hours to complete premixing. After that, the sol was added to the previous ZnO ethanol mixture at a ratio of 1:1, and continued to stir for 1h to ensure uniform mixing, a certain amount of hexamethyldisilazane was added to the mixture, and continued to stir for 4h, and the mixture prepared above was also centrifuged at a speed of 5000rpm, and washed three times with ethanol and deionized water, and dried to obtain multi-scale hydrophobic SiO2@ZnO particles.
[0053] 2. Prepare SiO2@ZnO white slurry:
[0054] Prepare silica sol with pH = 4 as a binder, set the pigment-to-base ratio to 1:5, set the speed of the cutting mixer to 3000 rpm, stir at room temperature for 2 hours, select aluminum alloy as the metal substrate, and ultrasonically clean the sandblasted aluminum alloy substrate with acetone and anhydrous ethanol. After the slurry is evenly stirred, it is evenly coated on the aluminum alloy substrate by scraping. The coating thickness is 150 μm and cured in an oven at 80°C for 4 hours.
[0055] Example 3: SiO2@ZnO-C coating
[0056] 500nm ZnO was selected as the pigment matrix, 20g ZnO was uniformly dispersed in 60g ethanol, ammonia water and tetraethyl silicate were mixed, pH was adjusted to 10 to prepare a sol, and the sol was further stirred for 2 hours to complete premixing. After that, the sol was added to the previous ZnO ethanol mixture at a ratio of 3:1, and continued to stir for 2 hours to ensure uniform mixing, a certain amount of hexamethyldisilazane was added to the mixture, and continued to stir for 5 hours, and the mixture prepared above was also centrifuged at a speed of 5000rpm, and washed three times with ethanol and deionized water, and dried to obtain multi-scale hydrophobic SiO2@ZnO particles.
[0057] 2. Prepare SiO2@ZnO white slurry:
[0058] Prepare silica sol with pH = 4 as a binder, set the pigment-to-base ratio to 1:5, set the speed of the cutting mixer to 5000 rpm, and stir at room temperature for 2 hours. Select aluminum alloy as the metal substrate, and ultrasonically clean the sandblasted aluminum alloy substrate with acetone and anhydrous ethanol. After the slurry is evenly stirred, it is evenly coated on the aluminum alloy substrate by scraping. The coating thickness is 150 μm and cured in an oven at 80°C for 4 hours.
[0059] For the coating prepared in the above embodiment, the following tests were performed:
[0060] Solar spectrum absorption test: The absorption of sunlight by the SiO2@ZnO-A coating prepared in Example 1 was tested. The test showed that the SiO2@ZnO-A coating had good reflective properties in the solar spectrum band, with an average absorption rate of 13.42, which has reached the reflective performance of commercial coatings in the solar spectrum band.
[0061] Infrared emission measurement: The absorption of sunlight by the ZnO200-20-A coating prepared in Example 1 was tested. The test showed that the SiO2@ZnO-A coating had good spectral emission performance with an average reflectivity of 92.38, which has reached the infrared emission performance of commercial coatings.
[0062] Coating adhesion test: First, cut 11 parallel cuts with equal spacing of 1mm on the test piece coating, and then cut the same number of cuts and spacing as the previous cuts vertically. After cutting, 25 or 100 squares will appear on the test plate. Use a soft brush to gently brush off the chips along the two diagonal directions of the squares, and then check and evaluate the coating adhesion. The test results show that the SiO2@ZnO-A coating has good coating adhesion.
[0063] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essential content of the present invention.
Claims
1. A method for preparing a SiO2@ZnO white dustproof coating based on a step-by-step sol-gel method, characterized in that: The following steps are involved: Step 1, uniformly dispersing ZnO in anhydrous ethanol to obtain a ZnO dispersion; Mixing ammonia water and tetraethyl silicate, adjusting the pH value and stirring evenly to obtain a sol; Then, the sol is added into the ZnO dispersion and stirred evenly; Step 2, then add a low surface energy modifier, continue stirring for a certain period of time, centrifuge, wash with anhydrous ethanol and deionized water in turn, and dry to obtain hydrophobic SiO2@ZnO particles; Step 3, mixing the hydrophobic SiO2@ZnO particles with the silica sol, adding a surfactant, and stirring evenly to obtain a slurry; Step 4: After the metal substrate is cleaned, the slurry is evenly scraped on the metal substrate and cured to obtain the coating.
2. The method according to claim 1, characterized in that: In step 1, the pH value of the sol is 8-10; the ZnO particle size is 200nm-600nm, and the mass ratio of zinc oxide to the sol is 3:1-1:
3.
3. The method according to claim 1, characterized in that: The low surface energy modifier is hexamethyldisilazane, heptadecafluorodecyltrimethoxysilane or octadecyltriethylsilane.
4. The method according to claim 1, characterized in that: The concentration of the low surface energy modifier is 1 wt% to 5 wt%.
5. The method according to claim 1, characterized in that: In step 3, the pH of the silica sol is 2-5.
6. The method according to claim 1, characterized in that: In step 3, the pigment-to-base ratio is 1:1-1:
5.
7. The method according to claim 1, characterized in that: In step 3, the surfactant is polyvinylpyrrolidone (PVP), cetyltrimethylammonium bromide (CTAB) or cetyltrimethylammonium chloride (CTAC).
8. The method according to claim 1, characterized in that: In step 4, the metal substrate is an aluminum alloy, a titanium alloy or a magnesium alloy; and the coating thickness is 100-300 μm.
9. The method according to claim 1, characterized in that: In step 4, the curing temperature is 60-100°C.
10. A SiO2@ZnO white dust-proof coating prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-reflectivity filler, inorganic thermal control coating thereof and preparation method of inorganic thermal control coating
CN116082877A
Dustproof adhesion self-cleaning ZnO double-layer white coating applied to lunar surface and preparation method of dustproof adhesion self-cleaning ZnO double-layer white coating
CN118440548A
Cited By
Rapid preparation method of charged lunar dust protection thermal control structure suitable for large-area application
CN120286323A